Paracrine Neuroprotective Effects of Neural Stem Cells on Glutamate-Induced Cortical Neuronal Cell Excitotoxicity - Mohammad Hossein Geranmayeh; Ali Baghbanzadeh; Abbas Barin; Jamileh Salar-Amoli; Mohammad Mehdi Dehghan; Reza Rahbarghazi; Hassan Azari (Tabriz University of Medical Sciences, 2015)
Purpose: Glutamate is a major excitatory neurotransmitter in mammalian central nervous system. Excessive glutamate releasing overactivates its receptors and changes calcium homeostasis that in turn leads to a cascade of intracellular events causing neuronal degeneration. In current study, we used neural stem cells conditioned medium (NSCs-CM) to investigate its neuroprotective effects on glutamate-treated primary cortical neurons. Methods: Embryonic rat primary cortical cultures were exposed to different concentrations of glutamate for 1 hour and then they incubated with NSCs-CM. Subsequently, the amount of cell survival in different glutamate excitotoxic groups were measured after 24 h of incubation by trypan blue exclusion assay and MTT assay. Hoechst and propidium iodide were used for determining apoptotic and necrotic cell death pathways proportion and then the effect of NSCs-CM was investigated on this proportion. Results: NSCs conditioned medium increased viability rate of the primary cortical neurons after glutamate-induced excitotoxicity. Also we found that NSCs-CM provides its neuroprotective effects mainly by decreasing apoptotic cell death rate rather than necrotic cell death rate. Conclusion: The current study shows that adult neural stem cells could exert paracrine neuroprotective effects on cortical neurons following a glutamate neurotoxic insult.